Marker Biokimia Penyakit Talasemia-β: Tinjauan Sistematis tentang Diagnosis, Pemantauan, Anemia, Ferritin, Hepcidin, MCV, dan MCHC - Assha Luthfianie; Lantip Rujito (Pusat riset dan Inovasi Nasional, 2025)
Thalassemia is a genetic disorder characterized by impaired hemoglobin synthesis. This disease is caused by mutations in the globin gene, leading to disrupted production of globin chains. As a result, the red blood cells produced are dysfunctional and have a shorter lifespan, causing anemia. This condition requires proper medical management, including blood transfusions and other treatments. One way to detect and monitor the progression of thalassemia is by using biochemical markers that can identify changes in the patient’s body. Therefore, the aim of this systematic literature review is to identify biochemical markers that can be used for the diagnosis and monitoring of thalassemia. The literature used in this study includes articles on human thalassemia research published in the last 10 years. Literature searches were conducted in several academic databases using relevant keywords such as “biochemical markers for thalassemia,” “diagnosis of thalassemia,” and “thalassemia monitoring.” Based on the search results, several biochemical markers related to thalassemia were identified, including hepcidin, ferritin, and lipid profile. Ferritin plays a role in monitoring iron levels, which are often elevated in thalassemia patients, while hepcidin regulates iron homeostasis in the body. Additionally, other components involved in thalassemia diagnosis and monitoring include Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), Mean Corpuscular Hemoglobin Concentration (MCHC), and hemoglobin levels. The findings of this systematic literature review are expected to provide a comprehensive overview of biochemical markers that can be used in the diagnosis and monitoring of thalassemia. By identifying relevant markers, it is hoped that more accurate and effective diagnostic methods will be developed in the future, leading to better monitoring of thalassemia patients.